Pengaruh Struktur Modal, Pertumbuhan Penjualan dan Arus Kas Operasi terhadap Harga Saham - Nurul Fadhilah; Afridayani Afridayani (Jurnal Syntax Admiration, 2024)
This study looks at how capital structure, sales growth, and operating flow have an impact on stock prices. The purpose of this study is to see how capital structure, sales growth, and operating flow have an impact on stock prices simultaneously and partially. This study uses a quantitative descriptive scheme. Non-cyclical consumer companies listed on the IDX during the period 2018–2022 are the subjects of this study. Using the purposive sampling technique, this study was quantitative descriptive and collected 18 samples of companies over five years, which resulted in 90 observational data with secondary data. Data analysis includes descriptive statistics and panel data regression tests. The results show that, overall, capital structure, sales growth, and operating cash flow affect stock prices; Only the capital structure affects the price partially, and the growth of sales and operating cash flow does not affect the price significantly.